Digital Revitalization of Traditional Arts at The Tjipta Boedaja Art Center In Magelang (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
The Digital Traditional Arts Creative Class Program is a community service activity that aims to revitalize performing arts and strengthen the capacity of young people at the Tjipta Boedaja Art Center in Magelang, through the integration of traditional arts and digital technology. This activity was motivated by the declining interest of young people in traditional arts, as well as limitations in digital documentation and intellectual property rights (IPR) protection. The program was implemented using a Participatory Action Research (PAR) approach through the stages of socialization, training, mentoring, and implementation. The results of the activity showed an increase in the participants' mastery of basic traditional dance movements and exploration of folk dance, as well as an increase in the center's social media activity of ±20% compared to before the program. In addition, the program produced an ISBN-registered traditional arts learning module and developed an official website as a center for archives and digital branding. The limitations of the program lie in the relatively short duration of mentoring and the limited coverage of participants. In the future, this program has the potential to be developed through continuous mentoring and broader digital platform integration to strengthen the sustainability of traditional arts.